Rare glomangiosarcoma of the tongue. (3rd July 2018) - Rajendran, Sumetha; Henderson, Arthur Harry; Gillett, Stuart
Abstract : The glomus tumour is a rare neoplasm derived from the glomus apparatus. Subungual sites are most common with only three published cases involving the dorsal tongue. To our knowledge, this is the first case of an intraoral malignant glomus tumour (glomangiosarcoma) to be published in English literature. We report a case of a single glomus tumour located on the posterior dorsal tongue of a middle-aged man, which was surgically excised. Immunohistological features were indicative of a glomus tumour; however, in this case, malignant features were also discovered, warranting re-excision.